CRITICAL THINKING SKILL OF THE ELEVEN SCIENCE STUDENTS ON CHEMICAL EQUILIBRIUM IN THE SENIOR HIGH SCHOOL OF INTERNATIONAL SCHOOL PREPARATION PROGRAMS (RSBI) - setiowati setiowati; ila rosilawati; noor fadiawati (Universitas Lampung, 2012)
This study purpose to describe critical thinking skill of the eleven science students in senior high school of international school preparation programs (RSBI) on chemical equilibrium leason. This study is qualitative study to the type of phenomenological study. This study is used essaies test, questionnaires, dan interviews manual. Subjects of this study are 32 students in class XI science 1 of Senior High School State 1 Kotagajah, 25 students in class XI science 6 of Senior High School State 1 Metro and 30 students in class XI science 5 of Senior High School State 9 Bandar Lampung.The result of this study show that four idicators of critical thinking that are answer question “Why”, judging the credibility of procedures, interpretation of statements, and making conclusion base on facts get average-value in a row 66,89; 68,26; 68,25 and 72,22 that all of it are in good criteria and thenindicator of making conclusion base on facts get the highest average-value. Students in high category, medium category and low category get average-value in a row 75,14; 69,77 and 62,47 all of it are in good criteria and then students in high category have critical thinking skill better than the other category. Critical thinking abilities rate of the eleven science students in senior high school of international school preparation programs (RSBI) are in good criteria. Keyword: Critical Thinking Skill, Chemical Equilibrium, International School Preparation Programs (RSBI)